2021
DOI: 10.3389/fphar.2021.653901
|View full text |Cite
|
Sign up to set email alerts
|

Bawei Chenxiang Wan Ameliorates Cardiac Hypertrophy by Activating AMPK/PPAR-α Signaling Pathway Improving Energy Metabolism

Abstract: Bawei Chenxiang Wan (BCW), a well-known traditional Chinese Tibetan medicine formula, is effective for the treatment of acute and chronic cardiovascular diseases. In the present study, we investigated the effect of BCW in cardiac hypertrophy and underlying mechanisms. The dose of 0.2, 0.4, and 0.8 g/kg BCW treated cardiac hypertrophy in SD rat model induced by isoprenaline (ISO). Our results showed that BCW (0.4 g/kg) could repress cardiac hypertrophy, indicated by macro morphology, heart weight to body weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…It has been proved that PPAR-α activation during the pressure overloaded HF induction can improve cardiac function and energy. In addition, PPAR-α also participates in the signaling cascades driven by AMPK [ 28 , 33 , 34 ]. In accordance with previous studies, PPAR-α, PGC-1α, CD36, CPT-1, and ACADM levels were decreased in the HF group, compared to that in the sham control group.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proved that PPAR-α activation during the pressure overloaded HF induction can improve cardiac function and energy. In addition, PPAR-α also participates in the signaling cascades driven by AMPK [ 28 , 33 , 34 ]. In accordance with previous studies, PPAR-α, PGC-1α, CD36, CPT-1, and ACADM levels were decreased in the HF group, compared to that in the sham control group.…”
Section: Discussionmentioning
confidence: 99%
“…Ensuring the blood supply recovery of the ischemic myocardial tissue is an important goal in the efforts to prevent or alleviate MI/RI. As an essential component of traditional Chinese medicines, TTMs have advantages in terms of their efficacy and fewer side effects due to their many targets, which make them unique in the treatment of cardiovascular disease [ 22 , 23 ]. In our previous study, we found that O. falcata extract demonstrated significant protective effects against MIRI, but the underlying mechanism is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…A study has proved that BCW inhibits cardiac hypertrophy by increasing the expression of CPT-1b, P-AMPK, AMPK, and PPAR-α proteins in ISO-induced cardiac hypertrophy rats. The results indicated the anti-cardiac hypertrophy effects of BCW were linked to the amelioration of disturbance in fatty acid metabolism (Zhang et al, 2021). Shensong Yangxin Capsule (SSYX) is a traditional Chinese medicine which has long been used in China to treat cardiac diseases.…”
Section: Cardiac Hypertrophymentioning
confidence: 99%